2001
DOI: 10.1007/s004670000497
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring cardiovascular changes during hemodialysis in children

Abstract: Hemodialysis (HD) causes rapid volume shifts and circulatory changes. In chronic renal failure (CRF) Na+/K+ATP-ase is depressed, whereas endogenous digoxin-like factor (EDLF) is elevated. Our aim was to characterize HD-induced cardiovascular adaptation and its possible links to Na+/K+ATP-ase and EDLF. Eleven children with CRF on HD (aged 14.7 +/- 3.7 years) and 11 healthy children were investigated for basic circulatory parameters. Thoracic impedance (Zo) and circulatory parameters were monitored by impedance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…[17][18][19][20] Use of ICG to monitor hemodynamic changes during laparoscopy and hemodialysis in children has also demonstrated that ICG can track the hemodynamic changes accurately during the procedure. 9,10 In our validation study of 12 children, we have shown that ICG monitoring of CO correlates well with the CO measured by the TD technique in children. 21 Potential limitations in the use of ICG are conditions in which the HR is greater than 250 beats/min, severe aortic valve regurgitation, an extremely high BP (mean arterial pressure >130 mm Hg) and in patients whose circulation is supported by an intra-aortic balloon pump.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…[17][18][19][20] Use of ICG to monitor hemodynamic changes during laparoscopy and hemodialysis in children has also demonstrated that ICG can track the hemodynamic changes accurately during the procedure. 9,10 In our validation study of 12 children, we have shown that ICG monitoring of CO correlates well with the CO measured by the TD technique in children. 21 Potential limitations in the use of ICG are conditions in which the HR is greater than 250 beats/min, severe aortic valve regurgitation, an extremely high BP (mean arterial pressure >130 mm Hg) and in patients whose circulation is supported by an intra-aortic balloon pump.…”
Section: Discussionmentioning
confidence: 75%
“…[4][5][6][7][8] There are reports of ICG use in children to monitor hemodynamic changes during surgical procedures and hemodialysis. 9,10 However, the use of ICG to evaluate the effects of erythrocytapheresis on hemodynamic changes in children with sickle cell disease (SCD) has not been reported.…”
mentioning
confidence: 99%
“…The present study demonstrated a decrease in MFV of MCA and PCA by 32% and 28%, respectively, in nondialysis day among non-diabetic ESRD on regular HD, which may carry high risk of increase prevalence of cerebrovascular stroke among HD patients Previous studies observed cerebral blood flow changes during hemodialysis session that may be contributed to many intra-dialytic cycle factors as rapid volume ultrafiltration, transient hypotension, changes in electrolytes, and cerebral water content or arterial hypoxemia that may induce possible subtle brain damage [1,6,7]. Thus, the worst time to communicate with dialysis patients may be during the hemodialysis sessions [8].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of uremic arteriopathy has also been demonstrated in children with ESKD [34] [35]. However, large volume ultra-filtration during hemodialysis in a short period of time, results in diminished cardiac filling, and decreased tolerance for dialysis [36]. Therefore, there are wide fluctuations in BP in children with ESKD on hemodialysis, making it difficult to define acceptable limits.…”
Section: Discussionmentioning
confidence: 99%